2012
DOI: 10.1128/jb.01013-12
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the Phthiocerol Dimycocerosate Biosynthetic Pathway by Rifampin-Resistant,rpoBMutant Mycobacterium tuberculosis

Abstract: h Multidrug-resistant tuberculosis has emerged as a major threat to tuberculosis control. Phylogenetically related rifampin-resistant actinomycetes with mutations mapping to clinically dominant Mycobacterium tuberculosis mutations in the rpoB gene show upregulation of gene networks encoding secondary metabolites. We compared the expressed proteomes and metabolomes of two fully drug-susceptible clinical strains of M. tuberculosis (wild type) to those of their respective rifampin-resistant, rpoB mutant progeny s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
91
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 79 publications
4
91
0
Order By: Relevance
“…LC-MS-based metabolomics showed differences in the metabolic profile of rifampin-resistant M. tuberculosis: 99 molecular features are different in the rifampin-resistant strains. In addition, the studies showed the major role of rpoB mutations in the M. tuberculosis metabolism (46).…”
Section: Metabolomics and Diagnostic Biomarkersmentioning
confidence: 99%
“…LC-MS-based metabolomics showed differences in the metabolic profile of rifampin-resistant M. tuberculosis: 99 molecular features are different in the rifampin-resistant strains. In addition, the studies showed the major role of rpoB mutations in the M. tuberculosis metabolism (46).…”
Section: Metabolomics and Diagnostic Biomarkersmentioning
confidence: 99%
“…Transcriptomic analysis of M. tuberculosis after rpoB mutation likewise demonstrates durable transcriptional change in this species (12,13). However, the specific downstream conse-* This work was supported by National Institutes of Health Grants U19 AI076217, U19 AI111224, R01 AI049313, and P30 AI060354 and the Burroughs Wellcome Foundation.…”
mentioning
confidence: 99%
“…Cells and culture filtrate were harvested after three weeks of culture as described elsewhere [14]. Culture…”
Section: Proteomic Analysismentioning
confidence: 99%
“…and used to qualify and provide similar biological reagents to the mycobacteria research community through BEI resources (https://www.beiresources.org/About/QualityControl.aspx). Before the digestion of proteins, the CW fraction was delipidated as described elsewhere [14]. All the resulting proteins were resuspended in 10mM ammonium bicarbonate (Sigma-Aldrich, A6141, US).…”
Section: Proteomic Analysismentioning
confidence: 99%
See 1 more Smart Citation